Determinant Factors of Earnings Management in Islamic Banks in Indonesia - Siti Auliyanti Nurbach; Rossje V. Suryaputri; Sri Wahyuningsih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study expects to analyze impact corporate governance (sharia supervisory board and audit committee) and directors’s diversity based on age, gender, and education level on earnings management, as well as examine the role of financial distress in moderating corporate governance. This study involves auxiliary information as yearly reports of Islamic banks enlisted with OJK during the 2015-2019 period with an aggregate of 62 examples. The analysis utilized in this study is a moderation regression analysis model. The discoveries of this study demonstrate that the sharia supervisory board has no negative effect on earnings management. Then, the audit committee has a negative influence on earnings management. Meanwhile, the diversity of the board in terms of age, gender, and education level has no effect on earnings management. This study also proves that the moderating does not strengthen of the sharia supervisory board on financial distress on earnings management only has an interaction. Meanwhile, the moderation of financial distress shows that it does not strengthen the negative influence of the audit committee on earnings management. The implications of the results of this study will increase the awareness of stakeholders about the implementation of corporate governance and the diversity of top management in Islamic banks to reduce earnings management actions.